MORE THAN JUST A COACH: A CASE STUDY OF THE COACH’S ROLE AS A PROVIDER OF SOCIAL SUPPORT FOR PENCAK SILAT ATHLETES: English - Kasyfillah, Muhammad Haidarsyah; Setiawati, Farida Agus; Nurhayati, Siti Rohmah; Herwin, Herwin (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
This study aims to examine the role of the coach as a social support provider who is closest to athlete and influential in providing both technical direction and moral guidance to the athletes he trains. The social support provided by the coach can have a positive impact on athletes both when competing and in everyday life. The method used in this research is qualitative with a case study approach, involving three pencak silat coaches as resource persons with semi-structured interviews. The results showed that pencak silat coaches have an important role in shaping the character of the athletes they train, both before and during competition. The social support provided by the coach is not only limited to technical material. However, character and moral development is very important to be applied as a fighter who is not only skilled in martial arts but also has good ethics in his daily life both in the family environment or the surrounding community. In addition, it can also improve the competing performance of pencak silat athletes to have mental toughness, self-confidence and optimism when competing in championships